The Economic Community of West African States : Fiscal Revenue Implications of the Prospective Economic Partnership Agreement with the European Union - Zouhon-Bi, Simplice G.; Nielsen, Lynge (World Bank, Washington, DC, 2012)
This paper applies a partial equilibrium model to analyze the fiscal revenue implications of the prospective economic partnership agreement between the Economic Community of West African States (ECOWAS) and the European Union. The authors find that, under standard import price and substitution elasticity assumptions, eliminating tariffs on all imports from the European Union would increase ECOWAS' imports from the European Union by 10.5-11.5 percent for selected ECOWAS countries, namely Cape Verde, Ghana, Nigeria, and Senegal. This increase in imports would be accompanied by a 2.4-5.6 percent decrease in total government revenues, owing mainly to lower fiscal revenues. Tariff revenue losses should represent 1 percent of GDP in Nigeria, 1.7 percent in Ghana, 2 percent in Senegal, and 3.6 percent in Cape Verde. However, the revenue losses may be manageable because of several mitigating factors, in particular the likelihood of product exclusions, the length of the agreement's implementation period, and the scope for reform of exemption regimes. The large country-by-country differences in fiscal revenue loss suggest that domestic tax reforms and fiscal transfers within ECOWAS could be important complements to the agreement's implementation.